SUBSTANTIATING ENVIRONMENTALLY FRIENDLY METHOD TO IMPROVE ENERGY EFFICIENCY OF PREMISES FOR KEEPING NURSING SOWS - Nebylytsia, M. S. (Scientific Progress & Innovations, 2020)
Improving energy efficiency of sow-houses, in the process of designing the reconstruction, is of practical importance for production. This is due to the fact that in Ukraine there are pig farms and complexes, which were designed mainly according to construction standards of 1995. The aim of this study was to justify environmentally friendly method to increase energy efficiency of premises for milking sows and to develop an algorithm for its determining. General scientific (experiment, analysis, synthesis) methods were applied in solving the tasks. In addition, the main microclimate parameters and temperature of the building depending on the seasons of the year were investigated. Geometric, heat engineering and energy characteristics of the sow-house were determined. It was found that the pigsty was characterized by a high value (0.54 m-1) of compactness index. At the same time, the mass heat capacity of enclosing constructions, per 1 m3 of ventilated volume, made only 0.08 MJ per 1 0 K, which indicated insufficient heat resistance of the house. As a result, in winter, at an average daily outdoor temperature of minus 2.9 0C, the indoor temperature dropped to 16.7 0C. Thus, it was 1.30C below the minimum admissible value, according to the VNTP-AIC-02.05 standard. Performance indicators of milking sows showed a significantly higher value of the average live weight of piglets at weaning by 0.19 kg in spring and 0.29 kg in summer, as compared with winter (p<0.05 and 0.01). At the same time, preservation of piglets litter before weaning was by 3.8–4.6 %. higher The economic efficiency of external wall insulation with ecologically safe Technofas effect heat-insulating material having a thickness of 50 mm was substantiated. An algorithm for determining energy efficiency the sow-house was developed. It is determined by the total annual consumption of energy, expressed in kW•h, divided by the value of the ventilated volume and annual turnover rate ratio of one individual stall place. It has been determined that walls’ thermal insulation of the heated pigsty contributes to improving its energy characteristics by 23.2 %. The estimated payback period in case of wall isolation with thermal insulation material will be 39.3 months. In addition, thermal insulation is environmentally important in saving 21.15 thousand kW/h of specific heat consumption. This is equivalent to approximately 7.42 tons of conventional fuel.